Anatomy and blood supply of the sternum - Neuhuber, Winfried; Lyer, Stefan; Alexiou, Christoph; Buder, Thomas (Deep Sternal Wound Infections, 2017)
The sternum is a sword-shaped flat bone about 15-17 cm long in the adult (? Fig. 2.1) (Putz and Müller-Gerbi Benninghoff 2003; Williams and Warwick 1980). Its cranial part, the manubrium, connects to the corpus by a synchondrosis in 90% of adults; in the remaining 10% there is a bony fusion (synostosis).
CRIS-Team Scopus Importer:2022-06-27
Keywords: Alba; Corti; Iodine; Ster; Synostosis